The linkages of energy, water, and land use in Southeast Asia: Challenges and opportunities for the Mekong region - Kim Hang Pham Do; Ariel Dinar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper aims to contribute to understanding the existing knowledge gaps in the linkages of energy, water, and land use in Southeast Asia and explores the political economy of energy transition in the Mekong region (MR). Investigating the struggle over hydropower development and decision-making on water and land across the region, this study shows that countries that are the winners or losers in the hydropower development schemes are not the only ones managing the Mekong; rather, it is part of the region-wide strategy of nations to sustain the MR. The analysis also explores the key issues involved in each nation, as the rush to acquire sources of alternative energy and other benefits to meet rapid growth demand has led to circumstances of risk within the MR. The relationship between MR cooperation programmes and China is a main concern, and the paper discusses the roles of issue linkages as a mechanism for achieving sustainable development.
Keywords: Q42; C78; D62; D74; 330; transboundary water resources; Mekong River; hydropower; issue linkages; externality games